Social physique anxiety, pregnancy and exercise : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Psychology at Massey University - Blind, Janet Mary (Massey University, 2004)
The purpose of this study was to examine SPA and exercise during and after pregnancy. Women enrolled in community ante-natal classes participated in the investigation (Exercisers n = 36; Non-exercisers n = 17). Participants completed the Social Physique Anxiety Scale (SPAS), Reasons for Exercise Inventory (REI), Exercise Behaviours and Preferences Scale and a modified Body Esteem Scale, and provided general demographic and exercise data during pregnancy and 6 weeks and 3 months post-pregnancy. Repeated measures ANOVA indicated that participant reasons for exercise changed significantly over the course of pregnancy from intrinsic to extrinsic, reflecting self-presentational motives. SPA has been found to be positively related to self-presentational motives in previous research, although significant results were not replicated in this study.
Keywords: Body image; Pregnancy; Exercise for pregnant women; Psychological aspects